2022
DOI: 10.1007/s11769-022-1321-1
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Exercise Efficiency to Evaluate the Accessibility and Capacity of Medical Resources in Tibet, China

Abstract: Accessibility and capacity of medical resources are key for the health care and emergency response, while the efficiency of the medical resources is very much limited by hypoxia in Tibet, China. Through introducing exercise efficiency, this study explores the accessibility of township residence to county-ship medical resources in Tibet using weighted mean travel time (WMT), and evaluates the medical capacity accordingly. The results show that: 1) the average travel time of township residence to county-level ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Consistent with the findings of existing research, this paper found that both territorial and potential accessibility tend to be unequal, which reveals that there are still many deficiencies in of accessibility in Tibet at the rapid development stage of transportation construction here (Gao et al., 2019; Wang et al., 2022; Wang et al., 2022b). However, there is still different from the conclusion that the fairness of accessibility at township level is declining (Gao & Sun, 2022).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with the findings of existing research, this paper found that both territorial and potential accessibility tend to be unequal, which reveals that there are still many deficiencies in of accessibility in Tibet at the rapid development stage of transportation construction here (Gao et al., 2019; Wang et al., 2022; Wang et al., 2022b). However, there is still different from the conclusion that the fairness of accessibility at township level is declining (Gao & Sun, 2022).…”
Section: Discussionsupporting
confidence: 87%
“…In other words, some indicators related to accessibility in Tibet may have not been included in the model, which needs to be further discovered and demonstrated with the help of clarification of influence path and field research. In the future, we can also further explore the transport accessibility of specific needs such as education or medical services, and then propose more targeted countermeasures (Wang et al., 2022b).…”
Section: Discussionmentioning
confidence: 99%